(untitled) (Research, Society and Development, 2025)
Objective: To analyze mortality from pneumonia-related hospitalizations among children and adolescents residing in the state of Mato Grosso from 2013 to 2023. Methods: This is an ecological study with a temporal design based on secondary data obtained from the SIH-DATASUS, covering notifications from January 2013 to December 2023. The study included individuals aged less than 1 year to 19 years. The analyzed variables were sex, age group, race/ethnicity, nature of care, establishment, health macro-region, year/month of processing, average length of stay, and deaths. Results: There were 61,918 hospitalizations of children and adolescents for pneumonia in Mato Grosso, with 440 hospital deaths, representing a monthly average of 3.33 deaths. Children under 1 year accounted for 43.4% of deaths. April recorded the highest number of deaths, with 54 cases and a case fatality rate of 0.74%. Mortality among boys was 25.64% higher compared to girls. In 2022, deaths exceeded the years with higher pneumonia incidence, possibly due to reduced innate immunity from lower pneumococcal exposure during social isolation in the pandemic. Conclusion: Pneumonia and its severe outcomes primarily affect children under 1 year, with higher incidence among males. Therefore, the importance of protective measures, such as updated vaccination schedules and breastfeeding promotion, stands out as fundamental strategies to reduce the high mortality rate observed in the state.